Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702460
|View full text |Cite
|
Sign up to set email alerts
|

Things That Make Us Reminisce

Abstract: Interactive devices can support personal remembering to benefit well-being. These designs require insight into what brings the past to mind, and how people relate to such cues. Prior work focused on mementos in the home; instead, this paper presents a diary and interview study of involuntary memory cueing in everyday life. Data was collected from fifteen adult individuals, using sentence completion diaries, combined with debriefing interviews. Qualitative analysis of the data showed that these participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A challenge for both methods is that their self-reported nature may compromise the accuracy and detail of the data. In diary studies, participants often self-report when it is convenient for them, and this retrospective recall may lead to reflections going unreported (Gennip, Hoven and Markopoulos 2015). Data capture may help with this, for example Gouveia and Karapanos (2013) explored lifelogging as an alternative to self-reported entries, where the participants were asked to review daily collections of media.…”
Section: In-situ Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A challenge for both methods is that their self-reported nature may compromise the accuracy and detail of the data. In diary studies, participants often self-report when it is convenient for them, and this retrospective recall may lead to reflections going unreported (Gennip, Hoven and Markopoulos 2015). Data capture may help with this, for example Gouveia and Karapanos (2013) explored lifelogging as an alternative to self-reported entries, where the participants were asked to review daily collections of media.…”
Section: In-situ Research Methodsmentioning
confidence: 99%
“…Where past research has identified that experience sampling, and diary studies can miss details of the contexts that are being explored (Csikszentmihalyi, Rathunde and Whalen 1993;Gennip, Hoven and Markopoulos 2015;, this method facilitates communication close to the time when the activity is occurring. We are interrupting people's activities and prompting reflection in the moment, trading off between participants' ability to recall and the intrusiveness of being asked about what you are doing.…”
Section: Contextual Inquirymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work in HCI has studied how digital technology can play a role in mediating reminiscence. Research on solitary reminiscence has explored how technology can be designed to support the categorisation of personal artefacts [17,54] or personal reflection over meaningful events [41,42,56]. In comparison, research on social reminiscence has explored how technologies such as multi-touch tabletops and photo viewers can provide families, young people and older adults with opportunities to interact around personal artefacts [1,24,43,55].…”
Section: Technology-mediated Reminiscencementioning
confidence: 99%
“…The qualities of possessions as external things that surround us throughout our day-to-day lives offer unique opportunities to exercise a level of control over our memories. Archiving, displaying or using possessions within the home that cue memories allows us to connect with the past, bringing it closer to the present or to store it away, giving us permission to forget [32,33]. As physical possessions age, they form patinas (a film, gloss or sheen) and traces of use that reinforce their shared history with the owner [28**,34].…”
Section: Connection Type 1 (C1): Possessions Can Acquire Memoriesmentioning
confidence: 99%